34m-512m=1

Simplify each term.

Combine 34 and m.

3m4-512m=1

Combine m and 512.

3m4-m⋅512=1

Move 51 to the left of m.

3m4-51m2=1

3m4-51m2=1

To write -51m2 as a fraction with a common denominator, multiply by 22.

3m4-51m2⋅22=1

Write each expression with a common denominator of 4, by multiplying each by an appropriate factor of 1.

Multiply 51m2 and 22.

3m4-51m⋅22⋅2=1

Multiply 2 by 2.

3m4-51m⋅24=1

3m4-51m⋅24=1

Combine the numerators over the common denominator.

3m-51m⋅24=1

Simplify the numerator.

Factor 3m out of 3m-51m⋅2.

Factor 3m out of 3m.

3m(1)-51m⋅24=1

Factor 3m out of -51m⋅2.

3m(1)+3m(-17⋅2)4=1

Factor 3m out of 3m(1)+3m(-17⋅2).

3m(1-17⋅2)4=1

3m(1-17⋅2)4=1

Multiply -17 by 2.

3m(1-34)4=1

Subtract 34 from 1.

3m⋅-334=1

3m⋅-334=1

Simplify the expression.

Multiply -33 by 3.

-99m4=1

Move the negative in front of the fraction.

-99m4=1

-99m4=1

-99m4=1

Multiply both sides of the equation by -499.

-499⋅(-99m4)=-499⋅1

Simplify -499⋅(-99m4).

Cancel the common factor of 4.

Move the leading negative in -499 into the numerator.

-499⋅(-99m4)=-499⋅1

Move the leading negative in -99m4 into the numerator.

-499⋅-99m4=-499⋅1

Factor 4 out of -4.

4(-1)99⋅-99m4=-499⋅1

Cancel the common factor.

4⋅-199⋅-99m4=-499⋅1

Rewrite the expression.

-199⋅(-99m)=-499⋅1

-199⋅(-99m)=-499⋅1

Cancel the common factor of 99.

Factor 99 out of -99m.

-199⋅(99(-m))=-499⋅1

Cancel the common factor.

-199⋅(99(-m))=-499⋅1

Rewrite the expression.

-1⋅(-m)=-499⋅1

-1⋅(-m)=-499⋅1

Multiply.

Multiply -1 by -1.

1⋅m=-499⋅1

Multiply m by 1.

m=-499⋅1

m=-499⋅1

m=-499⋅1

Multiply -1 by 1.

m=-499

m=-499

The result can be shown in multiple forms.

Exact Form:

m=-499

Decimal Form:

m=-0.04‾

Solve for m 3/4m-51/2m=1